Efficient Synthesis of Conformationally Restricted Apoptosis Inhibitors Bearing a Triazole Moiety. Issue 40 (13th August 2015) - Corredor, Miriam; Garrido, Maria; Bujons, Jordi; Orzáez, Mar; Pérez‐Payá, Enrique; Alfonso, Ignacio; Messeguer, Angel
Abstract Apoptosis is a biological process relevant to different human diseases that is regulated through protein–protein interactions and complex formation. Peptidomimetic compounds based on linear peptoids and cyclic analogues with different ring sizes have been previously reported as potent apoptotic inhibitors. Among them, the presence of cis/trans conformers of an exocyclic tertiary amide bond in slow exchange has been characterized. This information encouraged us to perform an isosteric replacement of the amide bond by a 1, 2, 3‐triazole moiety, in which different substitution patterns would mimic different amide rotamers. The syntheses of these restricted analogues have been carried out through an Ugi multicomponent reaction followed by an intramolecular cyclization. The unexpected formation of a β‐lactam scaffold prompted us to study the course of the intramolecular cyclization of the Ugi adducts. In order to modulate this cyclization, a small library of compounds bearing both heterocyclic scaffolds has been synthesized and their activities as apoptosis inhibitors have been evaluated.